2*f(x) + 3*f(1-x) = 4x-1

We notice that f(x) is a linear function:

==> let f(x) = ax+b

==> f(1-x) = a(1-x) + b = a - ax + b = -ax + a+b

Now substiute :

==> 2(ax+b) + 3(-ax+a+b) = 4x - 1

==> 2ax + 2b - 3ax + 3a + 3b = 4x-1

==> ax + 3a +5b = 4x - 1

**==> a= 4**

==> 3a + 5b = -1

==> 12 + 5b = -1

==> 5b = 11

**==> b= 11/5**

**==> f(x) = 4x + 11/5**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now